2018
DOI: 10.1186/s13287-018-0863-8
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet lysate in mesenchymal stromal cell expansion according to a GMP grade protocol: a cell factory experience

Abstract: BackgroundThe use of platelet lysate (PL) for the ex-vivo expansion of mesenchymal stromal/stem cells (MSCs) was initially proposed by Doucet et al. in 2005, as an alternative to animal serum. Moreover, regulatory authorities discourage the use of fetal bovine serum (FBS) or other animal derivatives, to avoid risk of zoonoses and xenogeneic immune reactions. Even if many studies investigated PL composition, there still are some open issues related to its use in ex-vivo MSC expansion, especially according to go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 36 publications
4
49
0
1
Order By: Relevance
“…Unlike in other studies, here ASCs were expanded using human platelet lysate in the culture media, which may have the advantage of avoiding the use of animal‐derived factors. Human platelet lysate is widely used to grow MSCs, and many studies have demonstrated that this confers a degree of safety that is at least equivalent to that offered by fetal bovine serum . Indeed, some studies have suggested that the use of platelet lysate may increase cell yield and shorten the time for ex vivo expansion without epigenetic alterations …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike in other studies, here ASCs were expanded using human platelet lysate in the culture media, which may have the advantage of avoiding the use of animal‐derived factors. Human platelet lysate is widely used to grow MSCs, and many studies have demonstrated that this confers a degree of safety that is at least equivalent to that offered by fetal bovine serum . Indeed, some studies have suggested that the use of platelet lysate may increase cell yield and shorten the time for ex vivo expansion without epigenetic alterations …”
Section: Discussionmentioning
confidence: 99%
“…Human platelet lysate is widely used to grow MSCs, [23][24][25] and many studies have demonstrated that this confers a degree of safety that is at least equivalent to that offered by fetal bovine serum. 26,27 Indeed, some studies have suggested that the use of platelet lysate may increase cell yield and shorten the time for ex vivo expansion without epigenetic alterations. 25,27 One of the issues regarding the use of somatic cell medicinal products has been the selection of the cell dose.…”
Section: Discussionmentioning
confidence: 99%
“…[14,29] This is reflected in the significantly higher metabolic activity of cells in HUink compared to the other two bioink materials (figure 5(c)). In addition, although in this study pooled PL batches were prepared in house, the increasing trend on the use of standardized clinical grade human PL as xeno-free alternative to animal-derived serum in cell culture, [30,31] represents an advantage over similar materials such as ECM bioinks (e.g. GelMA or decellurarised matrix), [11,32] which are typically of xenogenic origin, a significant barrier for clinical translation, and present high variability on the biochemical, topological and viscoelastic properties depending on the decellularization protocol.…”
Section: Bioprinting Performance and Biofunctionality Of Huinkmentioning
confidence: 99%
“…Quality controls for release testing of MSCs are related to safety, identity, purity and potency [61,62]. While some studies claim that hPL does not modify the immunomodulatory characteristics and the multipotency of MSCs [28,58,60,63], others show that there is a decrease in the immunomodulatory activity and surface marker modifications in BM-MSCs cultured with hPL [9,40,64].…”
Section: Considerations For Model-driven Cost-effective Process Transfermentioning
confidence: 99%